Tangeretin Improves the Memory of Swiss Mice, Suggesting Potential Molecular Interventions Through Animal Behavior Assessments and In Silico Studies - Md. Sakib Al Hasan; Mohd Shahnawaz Khan; Arusha Ayub; Raihan Chowdhury; Emon Mia; Md. Shadin; Md. Showkot Akbor; Muhammad Torequl Islam; Md. Shimul Bhuia (Brain and Behavior)
ABSTRACT Introduction Tangeretin (TAN), a polymethoxylated flavone from citrus peels, exhibits neuroprotective, anti‐inflammatory, and antioxidant properties. This study aims to evaluate the memory‐enhancing effects of TAN in Swiss mice and explore its potential molecular interactions with the D2 dopamine (DOP) receptor through in vivo behavioral assessments and in silico approaches. Methods Swiss mice were administered TAN (10 and 20 mg/kg), DOP (22 mg/kg), and olanzapine (OLN) (2 mg/kg), alone and in combinations per orally (p.o.), followed by cognitive assessments using marble burying, dust removal, and trained swimming tests. In silico studies included molecular docking against the D2 receptor (PDB: 6CM4), pharmacokinetics (SwissADME, pkCSM), and toxicity predictions (ProTox‐3). Results TAN significantly (p < 0.05) improved cognitive functions, including memory, anxiety, and motor coordination, in a dose‐dependent manner, with 20 mg/kg showing the most notable effect. The combination of TAN‐10 with DOP‐22 enhanced these benefits, whereas TAN‐10 with OLN‐2 reduced cognitive improvements. TAN‐treated Swiss mice showed better performance in marble burying, dust removal, and trained swimming tests, indicating enhanced memory, problem‐solving, and motor coordination. These results suggest TAN's potential in cognitive enhancement, particularly with DOP‐22. No deaths were observed in any treatment group, and all treated animals exhibited normal physiological activity with no signs of acute toxicity. In silico studies revealed that TAN exhibited the strongest binding affinity (BA) (−6.6 kcal/mol) with the D2 receptor, forming multiple hydrogen bonds (HBs), which indicates its potential mechanism for memory enhancement via dopaminergic modulation. Pharmacokinetic analyses also showed that TAN has favorable ADMET properties, including high gastrointestinal absorption, blood–brain barrier penetration, and low toxicity. Conclusion These findings highlight TAN's potential as a promising therapeutic candidate for memory‐related disorders, warranting further clinical exploration.